In Vitro Toxicity Assessment Of Synthetic Acaricides Against Yellow Mite, Polyphagotarsonemus Latus (Banks), And Predatory Mite, Amblyseius Ovalis (Evans), On Chilli Plants (Applied Biological Research, 2018)
The study was conducted to assess the toxic effect of topical use of different  synthetic acaricides on yellow mite (Polyphagotarsonemus latus) and its  predatory mite (Amblyseius ovalis). Both the mites were collected and  cultured separately on chilli plants grown in cups of 6 cm dia. during early  winter of 2014 and 2015, under ventilated glass-house conditions. Acaricide  application under laboratory conditions showed that fenpyroximate 5 EC @  1 mL L-1 and propargite 57 EC @ 2 mL L-1 were most toxic and caused  highest mortality of P. latus i.e. 98.2 and 96.8% with LC50 values of 12.09  and 21.95 ppm, respectively. The least mite reduction was shown by sulphur  80 WP (81.55%) with LC50 value of 210.3 ppm. Comparing the acaricides  applied, fenpyroxi-mate 5 EC and propargite 57 EC were less toxic to  predatory mites inflicting 49.1 and 54.1% mortality with respective LC50 values of 96.1 and 164.2 ppm.
Keywords: Acaricides; LC50; predatory mite; yellow mite; toxicity analysis